Unlocking urban potential : an assessment of the limitations found within external urban connectivity networks and amenity accessibility opportunities within Tshwane’s mixed-use precincts, to determine resident suitability - Devenish, Paul (University of Pretoria, 2024)
Mini Dissertation (MArch (Prof))--University of Pretoria, 2024.